Composition of constitutive heterochromatin of Pseudonannolene strinatii Mauriès, 1974 (Diplopoda, Spirostreptida) analyzed by AT/CG specific fluorochromes. - Campos, Kleber Agari; Fontanetti, Carmem Silvia (My University, 2005)
Triple staining with fluorochromes (DA/DAPI/CMA) and C-banding were used to characterize the composition of Pseudonannolene strinatii heterochromatin. C-banding showed C+ bands of different labeling intensity on chromosomes 1 and 2 in some cells. Fluorochrome staining revealed DAPI+ regions corresponding to the C-banding pattern, indicating that the heterochromatin of this species is abundant in AT-rich sequences.
Keywords: fluorescent dye; animal; arthropod; chromosome banding pattern; genetics; heterochromatin; karyotyping; methodology; Animals; Arthropods; Chromosome Banding; Fluorescent Dyes; Heterochromatin; Karyotyping